The large landowner as a visionary planner - Stéphane Sadoux (Angles)
The role of large landowners in planning processes has been largely ignored by scholars. This paper aims to fill part of the gap in literature. It focuses on a range of initiatives led by Lord Salisbury in the county of Hertfordshire. It seeks to show that these actions should be examined in the light of strategic planning issues due to the housing shortage, as large landowners are engaged in debates that occur upstream, well before construction effectively takes place. The paper also aims to demonstrate that Lord Salisbury’s initiatives are best understood when they are seen to exemplify a particular vision of human settlements. From a strategic point of view, this view involves the promotion of new settlements as a way of addressing the housing crisis and can thus be seen as a contemporary manifestation of Britain’s long tradition of planned communities. In design terms, it promotes traditional architecture and urbanism. The paper insists on the importance of the networks of stakeholders who share these views, and of the methods that allow them to be implemented.